Ana María Martínez de Sánchez, Cofradías y obras pías en Córdoba del Tucumán, Córdoba, Editorial de la Universidad Católica de Córdoba, 2006, 353 pp. - Frías, Susana R. (2007)
Fil: Frías, Susana R. Investigadora Independiente; Argentina